Thumbs up: A thematic analysis of image-based posting and liking behaviour on social media. Issue 7 (October 2018) - Lowe-Calverley, Emily; Grieve, Rachel
Highlights: Thematic analysis investigating thoughts prior to social media 'liking' and posting. Egoistic motivations were present in both posting and 'liking' behaviours. Users commonly considered the effect of their content or 'likes' on viewers. 'Liking' appears to truly indicate enjoyment and appreciation of content. Numerous considerations point to the importance of these simple online actions. Abstract: This study aimed to investigate the thoughts that social media users have prior to posting or 'liking' images on social media; particularly exploring the presence of egoistic, self-presentation considerations. Responses to two open-ended questions regarding considerations prior to posting ( n = 203) and 'liking' ( n = 195) images on social media were analysed using thematic analysis. Egoistic motivations influenced both posting and 'liking' an image on social media; suggesting an awareness that self-presentation can be affected (and therefore manipulated) through image posting and 'liking'. Users also considered who would see their content or behaviour, and the effect this might have on others. Finally, 'liking' actually represents liking, with enjoyment and image value considered prior to providing public, online appreciation.